EFISIENSI PAKAN, PERTUMBUHAN, KELANGSUNGAN HIDUP DAN RESPON IMUN IKAN PATIN (Pangasius sp.) YANG DIBERI PAKAN BERSINBIOTIK - Enromauli Pangaribuan; Ade Dwi Sasanti; Mohamad Amin (Universitas Sriwijaya, 2017)
ABSTRACTSynbiotic is a combination of probiotics and prebiotics can improve the feed efficiency, growth, survival and BAL population of fish. The purpose of this research was to know the effect of synbiotic feed to feed efficiency, growth, survival and immune response of catfish. This research conducted on October to December 2016 in Laboratorium Dasar Perikanan, Departement of Budidaya Perairan, Faculty of Agriculture, Sriwijaya University. The method used in the research is Completely Randomized Design (CRD) with six treatments and three replications. Catfish with synbiotic feed that treatment with the addition of commercial feed with synbiotic P0 (Control), P1 (2.5 ml Prebiotics + Probiotics 6 ml /kg), P2 (5.0 ml Prebiotics + Probiotics 6 ml /kg), P3 (7.5 ml Prebiotics + Probiotics 6 ml /kg), P4 (10.5 ml Prebiotics + Probiotics 6 ml /kg) and P5 (12.5 ml Prebiotics + Probiotics 6 ml /kg) for 30 days. The observed parameters were feed efficiency, growth, survival, BAL populations in the gut and clinical symptoms after challenge test. The results showed that provision addition of synbiotic in feed give significant effect to feed efficiency, growth and survival of catfish. The treatment P2 with synbiotic feed (5.0 ml Prebiotics + 6 ml Probiotics /kg) gives the feed efficiency (39,27%), the highest growth of weight (4.38 g), the highest growth of length (1.74 cm), the survival (97.78%), LAB (Lactid Acid Bacteria) population (3.51 x 104 CFU.mL-1) and survival after test challenge with A. hydrophila (86.67%). Keywords: Sinbiotic, Pakan, Pangaius sp, Aeromonas hydrophila